2006
DOI: 10.1103/physreve.74.016303
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale flow effects, energy transfer, and self-similarity on turbulence

Abstract: The effect of large scales on the statistics and dynamics of turbulent fluctuations is studied using data from high resolution direct numerical simulations. Three different kinds of forcing, and spatial resolutions ranging from 256 3 to 1024 3 , are being used. The study is carried out by investigating the nonlinear triadic interactions in Fourier space, transfer functions, structure functions, and probability density functions. Our results show that the large scale flow plays an important role in the developm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 66 publications
13
123
1
2
Order By: Relevance
“…The solenoidal contribution to the interface (2 km s −1 ) would exceed the possible compressive one (≤2 km s −1 ), in agreement with Federrath et al (2009), who found that our observed statistical properties of turbulence in the Polaris Flare are in good agreement with solenoidal forcing on large scales. This result is similar to the findings of Mininni et al (2006a) that the stronger the shear on large scales, the more intense the intermittency of velocity increments on small scales.…”
Section: What Is the Nature Of The Interface?supporting
confidence: 82%
See 1 more Smart Citation
“…The solenoidal contribution to the interface (2 km s −1 ) would exceed the possible compressive one (≤2 km s −1 ), in agreement with Federrath et al (2009), who found that our observed statistical properties of turbulence in the Polaris Flare are in good agreement with solenoidal forcing on large scales. This result is similar to the findings of Mininni et al (2006a) that the stronger the shear on large scales, the more intense the intermittency of velocity increments on small scales.…”
Section: What Is the Nature Of The Interface?supporting
confidence: 82%
“…Because it is supersonic, magnetized, and develops in a multiphase medium, interstellar turbulence is expected to differ from turbulence in laboratory flow experiments or in state-of-the-art numerical simulations, e.g., Chanal et al (2000) for experiments in gaseous helium and Mininni et al (2006a) or Alexakis et al (2007) for MHD simulations. Nonetheless, it may carry some universal properties of turbulence, such as space-time intermittency (for a review see Anselmet et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the T ± (K, Q) transfer functions do not give us direct information on the scales of the two fields z + and z − that interact and contribute to the energy cascade. To investigate the locality on nonlocality of the interactions between the two Elsässer counterpropagating waves, we introduce the partial fluxes (see [28,29]) defined as:…”
Section: Definitionsmentioning
confidence: 99%
“…Recently, MJ04 found that intense structures of vorticity and rate of strain are respectively filaments and ribbons that are not randomly distributed in space but that instead form clusters of inertial-range extent, implying a large-scale organization of the small-scale intermittent structures. In 1024 3 numerical simulations of incompressible turbulence, with variable large-scale stirring forces, Mininni et al (2006a) have shown that the large and small-scale properties of the flow are correlated, namely that i) more intense small-scale gradients and vortex tubes are concentrated in the regions where the large-scale shears are the largest, and that ii) the departure from the Kolmogorov scaling is more pronounced in these regions. They infer from these results that the statistical signatures of intermittency are linked to the existence of the small-scale vortex tubes.…”
Section: Introductionmentioning
confidence: 99%